Science for non scientists (2016)
Several processes have been advanced in the country, including the conceptualization of Social Appropriation of Knowledge (ASC) and in Medellin specifically programs and applications have been developed that allow citizens to take an interest in weather issues, among others, Explora Park has also played an important role.